Electromagnetic Compatibility of Compensating Devices and Converters of an Adjustable Electric Drive in Electrical Networks of Industrial Enterprises - V. P. Schasny; A. I. Zhukouski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The problems of reactive power compensation and improving the quality of electrical energy in the power supply systems of industrial enterprises are inseparable. Their relevance is due to the widespread use of electric receivers that consume reactive power and distort the quality of electrical energy in the network, as well as the implementation of new technologies, systems and equipment into production that make increased demands on the quality of electrical energy consumed. An important characteristic of the quality of electrical energy rationed by GOST 32144–2013 is the non-sinusoidal voltage. The main reason for the non-sinusoidal voltage in the electrical networks of industrial enterprises is the use of electrical equipment with a nonlinear voltage characteristic, which is a source of conductive electromagnetic interference, in particular: adjustable DC and AC electric drives, uninterruptible power supplies of electric receivers, electric welding equipment, electric arc furnaces, induction heating installations, gas-discharge radiation sources. Due to the nonlinearity of the current-voltage characteristics, the above devices consume a non-sinusoidal current from the network, which causes harmonic distortion of the supply voltage, including the fundamental harmonic component and higher harmonic components that are multiples of the fundamental frequency. Non-sinusoidal voltage, in turn, causes additional losses of power and energy in the elements of the electrical network, causes overheating and accelerated aging of the insulation of electrical equipment, reducing its operational reliability and reducing service life, worsens the accuracy of electrical measurements, causes malfunctions in automation systems, telemechanics, relay protection, electronic systems and communications. Non-sinusoidal voltage significantly complicates the compensation of reactive power in the electrical network. Compensating devices are made on the basis of capacitors, whose electrical parameters (resistance, power, current) depend on both the magnitude of the supply voltage and its harmonic composition. The present article identifies problems and proposes solutions in terms of reactive power compensation and improving the quality of electrical energy in electrical networks containing thyristor voltage converters and frequency converters used in adjustable electric drive installations of industrial enterprises.